2014
DOI: 10.1007/978-3-319-09704-6_26
|View full text |Cite
|
Sign up to set email alerts
|

Operational State Complexity under Parikh Equivalence

Abstract: Abstract. We investigate, under Parikh equivalence, the state complexity of some language operations which preserve regularity. For union, concatenation, Kleene star, complement, intersection, shuffle, and reversal, we obtain a polynomial state complexity over any fixed alphabet, in contrast to the intrinsic exponential state complexity of some of these operations in the classical version. For projection we prove a superpolynomial state complexity, which is lower than the exponential one of the corresponding c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…A summary of our results can be found in Table 1. The precise bound of the former result improves a recent result shown in [9], and the latter result on the complementation answers an open question stated in [9], too.…”
Section: Introductionsupporting
confidence: 83%
“…A summary of our results can be found in Table 1. The precise bound of the former result improves a recent result shown in [9], and the latter result on the complementation answers an open question stated in [9], too.…”
Section: Introductionsupporting
confidence: 83%
“…the Parikh image of the languages one can prove a better conversion bound. Namely, in [8] it was shown that for each NFA with n states a Parikh equivalent DFA with e O( √ n log n) states can be constructed and that this bound is asymptotically tight. Thus, in our setting this result reads as follows: Theorem 3.…”
Section: Variants Of Nondeterministic Jumping Finite Automatamentioning
confidence: 99%
“…The precise worst case state complexity of many basic language operations has been established; see e.g. [2,5,8,14,17,23,25,27,31,33,37]. Also there has been much work on the state complexity of combinations of basic language operations [3,7,9,10,18,32].…”
Section: Introductionmentioning
confidence: 99%